JUHŪD AL-ASYĀ’IRAH AL-MUĀSRĪN FĪ AL-TAQRĪB BAYN AL-AFKĀR AL-SUNNIYYAH: AL-SYAIKH HASAN AL-SYĀFI’Ī NAMŪŻAJAN - Mohamed, Nabil Fouly (Indonesian Journal of Islamic Literature and Muslim Society, 2020)
The article aims to describe Hasan al-Shafi’i’s view of uniting Sunnis theologically as an applied model. Through historical-philosophical analysis, this article found that Hasan al-Shafi’i viewed the need to unite Sunni viewpoints in the contemporary era. With his background in communication with the Islamic world and the West, Hasan al-Shafi’i confirmed the importance of understanding I’tidāl from al-Asy’ari theology. This theology rests on the spirit of harmony and tolerance, assuming that diversity is fairness and that plural life is the foundation of life that must be maintained. This view implies the restoration of theological relations between Sunni groups. Such a converged approach can serve as a model that is methodologically expected to enhance rapprochement on and off the Sunni spectrum